1994
DOI: 10.1152/jappl.1994.76.6.2611
|View full text |Cite
|
Sign up to set email alerts
|

Diphenyleneiodonium inhibits both potassium and calcium currents in isolated pulmonary artery smooth muscle cells

Abstract: Diphenyleneiodonium (DPI) blocks hypoxic vasoconstriction in the pulmonary vasculature. Because one of the actions of DPI is the inhibition of NADPH oxidase, this has led to the suggestion that NADPH oxidase acts as an oxygen tension sensor in pulmonary smooth muscle cells. We investigated the effects of DPI on potassium and calcium currents in freshly isolated pulmonary artery smooth muscle cells by using whole cell patch-clamp recordings, since these ionic currents are known to be involved in hypoxic pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 0 publications
3
42
0
2
Order By: Relevance
“…Moreover, experimental evidence suggests that the action of DPI and other iodonium-containing compounds is not restricted to flavoenzymes only. Indeed, DPI caused reversible blockade of K ϩ and Ca 2ϩ currents in isolated type I carotid body cells (12) and in pulmonary smooth muscle cells (13), indicating that DPI is a nonselective ion channel blocker. Both DPI and DIP have been found to be antagonists of the Nmethyl-D-aspartate receptors, through inhibition of opening processes of the ion channel (14); by this way, DIP protects neurons against glutamate toxicity (15).…”
Section: From the Department Of Genetics Biology And Biochemistry mentioning
confidence: 98%
“…Moreover, experimental evidence suggests that the action of DPI and other iodonium-containing compounds is not restricted to flavoenzymes only. Indeed, DPI caused reversible blockade of K ϩ and Ca 2ϩ currents in isolated type I carotid body cells (12) and in pulmonary smooth muscle cells (13), indicating that DPI is a nonselective ion channel blocker. Both DPI and DIP have been found to be antagonists of the Nmethyl-D-aspartate receptors, through inhibition of opening processes of the ion channel (14); by this way, DIP protects neurons against glutamate toxicity (15).…”
Section: From the Department Of Genetics Biology And Biochemistry mentioning
confidence: 98%
“…Moreover, a number of publications show that Nox inhibition by DPI, iodonium diphenyl, and aminoethylbenzenesulfonyl fluoride all reduce the acute hypoxiainduced increase in [Ca 2þ ] i and contraction in cultured rat PASMCs (118), and vasoconstriction in isolated calf pulmonary arteries (52) and in rabbit and rat lungs (22, 88, 110). However, the specificity of iodonium compounds as Nox inhibitors has been disputed, because these agents can inhibit the mitochondrial ETC in heart cells and voltage-dependent Ca 2þ currents in PASMCs (68,107). Whereas gp91 phox-=-mice show normal or reduced acute hypoxic responses (6,42,44), acute hypoxic vasoconstriction is inhibited in p47 phox-=-mice (112).…”
Section: Nadph Oxidase Is Involved In the Hypoxic Increase In [Ros] Imentioning
confidence: 99%
“…Ahluwalia (2) has indicated that Cl Ϫ current activated by cell swelling in human neutrophiles counteracts a depolarization induced by the NADPH oxidase. Furthermore, DPI has been reported to inhibit K ϩ channels in, e.g., isolated pulmonary smooth muscle cells (74) and type I cells from neonatal rat carotid body (76). To test whether inhibition of the volumesensitive K ϩ and Cl Ϫ channels would have an impact on the ROS production following hypotonic exposure, we estimated the change in fluorescence with time in NIH3T3 cells after hypotonic exposure in the absence and presence of tamoxifen and clofilium, which are recognized as potent blockers of the volume-sensitive Cl Ϫ and K ϩ channels, respectively (33,58).…”
Section: Catalytic and Regulatory Nadph Oxidase Subunits Expressed Inmentioning
confidence: 99%